Dual-architecture Internet supporting intelligent governance of cyber content - 杨鹏; 李幼平 (Tongxin xuebao)
For the current Internet architecture is suffering many challenges of cyber content governance,including big data trends of cyber contents,lack of semantic identification,and the severe situation of content security.In seeking to address these challenges,a dual-architecture Internet which integrated the current Internet architecture with a complementary secondary broadcast-storage network architecture characterized as the combination of broadcast transmission and ubiquitous storage was proposed.The design principles and core concepts of the dual-architecture Internet and its intelligent realization mechanism of cyber content governance were introduced,and especially,the national standard of uniform content label (UCL) and UCL-based rich semantic vector coding of contents,the gathering of popular contents the UCL-oriented security energy level model,the UCL knowledge space and content clustering hall for workshop of meta-synthetic engineering were detailed.Consequently,a prototype of dual-architecture Internet supporting intelligent governance of cyber contents was developed to verify the design principles and core concepts of the dual-architecture Internet and its capability for intelligent governance of cyber contents.The dual-architecture Internet proposed can provide a brand-new approach to solve the problem of cyber content governance from the high-level perspective of network architecture.